SURVEYING AND GEOINFORMATICS PROFESSION AND CONSTRUCTION INDUSTRY: A CASE STUDY OF BAZE UNIVERSITY TEACHING HOSPITAL (BUTH) ABUJA, NIGERIA - Morakinyo, Barnabas O.; Anselm, Jideofor Akubue (FUDMA Journal of Sciences, 2026)
The aim of this study is to examine the place of Surveying and Geoinformatics in the construction industry with BAZE University Teaching Hospital (BUTH) as a case study. The study adopts a practice-based case study approach drawing on Engineering Survey data, construction records, and site operations at BUTH. The major First Order Survey instruments used for the execution of the project are Differential Global Positioning System (DGPS), Leica 307 Total Station and Automatic Level. The angular misclosure recorded for the entire survey is 00o 01’ 30” while the linear accuracy for the survey is 1:12,281. The findings show that Surveying was involved from the planning to the completion and maintenance stages. Surveying input proved most critical at setting out or construction layout, foundation and construction stages. The scale of height variation was properly managed. The BUTH project shows that the early control establishment reduced the setting-out errors; and the continuous monitoring helped detect column deflections before they became structural issues. BUTH project show that Surveying is required to ensure the integrity and efficiency of any construction project is ascertained. Hence, it can be concluded that this study reinforces or illustrates the centrality of Surveying in the construction and building industry.